2017
DOI: 10.1103/physrevc.95.031601
|View full text |Cite
|
Sign up to set email alerts
|

How the Pauli exclusion principle affects fusion of atomic nuclei

Abstract: The Pauli exclusion principle induces a repulsion between composite systems of identical fermions such as colliding atomic nuclei. Our goal is to study how heavy-ion fusion is impacted by this "Pauli repulsion". We propose a new microscopic approach, the density-constrained frozen Hartree-Fock method, to compute the bare potential including the Pauli exclusion principle exactly. Pauli repulsion is shown to be important inside the barrier radius and increases with the charge product of the nuclei. Its main effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 66 publications
(117 reference statements)
3
110
3
Order By: Relevance
“…This is prominent in the region of [11][12][13][14][15][16] • , and it indicates the contribution of a third evaporation mode to the overall distribution. Analysis of the PACE4 output data suggests that this third component arises from the emission of two alpha particles [24].…”
Section: Deduced Angular Distributionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is prominent in the region of [11][12][13][14][15][16] • , and it indicates the contribution of a third evaporation mode to the overall distribution. Analysis of the PACE4 output data suggests that this third component arises from the emission of two alpha particles [24].…”
Section: Deduced Angular Distributionmentioning
confidence: 94%
“…In order to accommodate this inconsistency, a number of explanations have been put forward, including effects of energy dissipation both below and above the barrier [10], and the damping of quantum vibrations as the single-particle wavefunctions of the two nuclei mix [11]. The role of the incompressibility of nuclear matter has also been explored [12], while more recently, a microscopic approach to include the effects of Pauli repulsion has also been developed [13]. As modifications to the existing thee-mail: lauren.bezzina@anu.edu.au ory are suggested and new models of fusion arise, verification of these theories via experimental measurements will be required.…”
Section: Introductionmentioning
confidence: 99%
“…[29] showed that isovector terms (central and spin-orbit) were significant for density-constrained time-dependent Hartree-Fock (DC-TDHF) calculations of the nucleus-nucleus potential of the 40 Ca + 132 Sn system. As a preliminary study, frozen Hartree-Fock (FHF) [30][31][32][33] was used with the SQMC parameterisation for the same system. FHF calculations provide the bare nucleusnucleus potential from the Hartree-Fock ground-states, with no polarisation effects from dynamics.…”
Section: Fusionmentioning
confidence: 99%
“…The study of fusion cross sections both above and below the barrier has been performed for many systems using a * kyle.s.godbey@vanderbilt.edu † luguo@ucas.ac.cn ‡ umar@compsci.cas.vanderbilt.edu number of distinct techniques, though most approaches ultimately require a heavy-ion interaction potential as the starting point [6]. How one obtains such a potential is also varied, though two main classes can be roughly identified: phenomenological models [7][8][9][10][11][12][13][14][15][16] and (semi-)microscopic models [17][18][19][20][21][22][23][24][25][26]. Within each class there are myriad methods and assumptions, so we focus on the (semi-)microscopic class of methods which are more germane to the current work.…”
Section: Introductionmentioning
confidence: 99%